Two new species of the genera Pseudocandona and Cytherissa (Ostracoda, Podocopida) from the coastal zone of Lake Baikal - Alekseeva, Tatyana M.; Krivorotkin, Roman S.; Moore, Marianne V.; Timoshkin, Oleg A. (Zootaxa, 2025)
Most freshwater ostracods are endemic at either the local or regional level, and ancient lakes, such as Lakes Baikal and Tanganyika, are biodiversity hotspots for this group of organisms. Here we describe and name two new species of endemic ostracods from Lake Baikal in honor of Professors Stephanie Guildford and Robert Hecky who served as editors for the Journal of Great Lakes Research for 13 years. Illustrated descriptions of females and males of these two ostracod species of the genera Pseudocandona Kaufmann, 1900 and Cytherissa Sars, 1925—Pseudocandona guildfordae Alekseeva, Krivorotkin & Timoshkin sp. nov. and Cytherissa heckyi Alekseeva, Krivorotkin & Timoshkin sp. nov.—are presented and their habitats briefly described. These species were discovered when examining the ostracod collections of the famous Russian freshwater biologist, Prof. G.F. Mazepova.